Mitochondrial Dynamics: Biogenesis, Fission, Fusion, and Mitophagy in the Regulation of Stem Cell Behaviors - Wenyan Fu; Yang Liu; Hang Yin (Stem Cells International)
Stem cells have the unique capacity to differentiate into many cell types during embryonic development and postnatal growth. Through coordinated cellular behaviors (self-renewal, proliferation, and differentiation), stem cells are also pivotal to the homeostasis, repair, and regeneration of many adult tissues/organs and thus of great importance in regenerative medicine. Emerging evidence indicates that mitochondria are actively involved in the regulation of stem cell behaviors. Mitochondria undergo specific dynamics (biogenesis, fission, fusion, and mitophagy) during stem cell self-renewal, proliferation, and differentiation. The alteration of mitochondrial dynamics, fine-tuned by stem cell niche factors and stress signaling, has considerable impacts on stem cell behaviors. Here, we summarize the recent research progress on (1) how mitochondrial dynamics controls stem cell behaviors, (2) intrinsic and extrinsic factors that regulate mitochondrial dynamics, and (3) pharmacological regulators of mitochondrial dynamics and their therapeutic potential. This review emphasizes the metabolic control of stemness and differentiation and may shed light on potential new applications in stem cell-based therapy.